2017
DOI: 10.1007/s10815-017-1078-0
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in reproductive outcomes according to the endometrial preparation protocol in frozen embryo transfer

Abstract: In frozen embryo transfer, artificial cycles were associated with more early pregnancy loss and lower live birth rate than stimulated cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 19 publications
3
20
0
Order By: Relevance
“…Regarding the CPR and outcomes of abnormal implantation, a lower CPR and a higher risk of early pregnancy loss were discovered in AC-FET cycles compared to SC-FET. The results were also in accordance with previous retrospective study ( 8 ). On the one hand, letrozole use in SC-FET cycles reduces serum and intraovarian estrogens by blocking the synthesis of estrogen from androgens in the ovarian granulosa cells leading to optimal endometrial development, therefore better endometrium receptivity and improved CP ( 9 ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Regarding the CPR and outcomes of abnormal implantation, a lower CPR and a higher risk of early pregnancy loss were discovered in AC-FET cycles compared to SC-FET. The results were also in accordance with previous retrospective study ( 8 ). On the one hand, letrozole use in SC-FET cycles reduces serum and intraovarian estrogens by blocking the synthesis of estrogen from androgens in the ovarian granulosa cells leading to optimal endometrial development, therefore better endometrium receptivity and improved CP ( 9 ).…”
Section: Discussionsupporting
confidence: 93%
“…Our data added to the current body of evidence and was in line with the recent literatures which found adverse effect of artificial protocol used for scheduling FET on LBR (viable in Table S1) (6)(7)(8)(9). AC-FET has attracted attention as an effective protocol preparing endometrium for patients with regular or irregular menses cycles since AC-FET can reduce the need for repeated hospital visits and thus increase patient convenience (2,6,18).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Since then, several studies have compared the reproductive outcomes of endometrial preparation with stimulated cycles using gonadotropin and clomiphene or letrozole or both, with the artificial cycles. Notably, a number of studies have shown positive results involving ovarian stimulation (OS) for endometrial preparation in frozen embryo transfer cycles in PCOS patients [2,[8][9][10][11][12], and some studies have not found any differences compared with hormonal endometrial preparation [13,14].…”
Section: Introductionmentioning
confidence: 99%